Common reasons that lead to the development of pathologies of the gastrointestinal tract - Deekshith Battu (Journal of Science in Medicine and Life, 2024)
The main function of the digestive system is to perform vital functions in our body. Life is absolutely impossible without it, because thanks to its main processes (digestion of ingested nutrients and their absorption), a person receives the necessary energy for work and rest. The stomach and intestines are the main organs of digestion, and their activity is related to the initial and final stages of the entire digestive tract. If your stomach and intestines are healthy, they will never let you down. It is worth noting that the human digestive system is very sensitive. It immediately affects any, even small, changes in the internal environment of the entire body, as well as in the entire external world, which lead to various diseases of the gastrointestinal tract. They cause a lot of inconvenience to the patient: discomfort and pain.